Multiple timescasles in the fluctuations of the equatorial DST index through singular spectrum analysis - Rangarajan, G.K.; Araki, T. (My University, 1996)
The equatorial Dst index for the period 1957-1994 is analysed using the data-adaptive, noise-reducing technique of Singular Spectral Analysis (SSA) in many time scales covering annual, monthly, daily and hourly mean values. The salient features of the results are (i) the presence of a long term trend and a none-too-consistent and weak solar cycle variation in phase opposition with the solar activity, (ii) a well defined ∼44 month oscillation with almost constant amplitude throughout the period of analysis with no dependence on solar activity, (iii) an intermittantly strong quasibiennial oscillation with largest amplitudes in the recent years 1990-1993 and (iv) the consistent presence of annual variation with some amplitude modulation and a semiannual variation whose amplitude is independent of solar activity. Daily mean values of Dst, during an interval of intense recurrent activity, shows differences in its periodic behavior compared to the AE and Ap indices. An index of middle latitudes, recently proposed, is shown to behave somewhat differently from expectations probably because of inadequate compensation for the quiet day component. Storm time changes in Dst index, as brought out by the analysis of long-duration severe geomagnetic disturbances are characterised by periodicities of about 20 hours and 40 hours, in two separate spectral bands. This is suggested to be due to the corresponding fluctuations in the energy injection into the ring current. In most cases, the singular spectra indicate that only about 60 percent of the total variance in the Dst index could be accounted for by regular variations and the rest corresponding to a large noise floor in the spectra.
Keywords: Solar activity; Spectrum analysis; DST index; Equatorial dst index; Daily mean values